Pengaruh Asimetri Informasi, Ukuran Perusahaan, dan Profitabilitas Terhadap Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2009-2012 - Ivana Triany Putri; Haryetti '; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to examine information asymmetry, firm size, and profitability on earnings management in manufacturing companies listed in Indonesia Stock Exchange in period 2009-2012. This study uses earnings management as the dependent variable, as the independent variable by information asymmetry, firm size, and profitability. Purposive sampling method is used to get the sample, and from 153 firms that we observed, we get 80 firms as the samples. To analize the data Multiple Linier Regression, F-test and t-test analysis with are used SPSS 20. The results shows that the information asymmetry, firm size, and profitability variables simultaneously have no significant effect on earnings management. Meanwhile partially, only firm size that has significant effect on earning management.Keywords : Information Asymmetry, Firm Size, Profitability, and Earning Management